2010
DOI: 10.1007/s00125-010-1843-4
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial treatment increases endothelial progenitor cells in patients with type 2 diabetes

Abstract: Numbers of EPC derived from peripheral blood mononuclear cells increased significantly after multifactorial intervention in type 2 diabetic patients. It remains to be shown whether these changes contribute to the beneficial effects of multifactorial intervention on diabetic micro- and macroangiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
1
23
2
1
Order By: Relevance
“…Enrolling 74 patients with type Ⅰ diabetes, EPCs counts were significantly lower in these patients compared to 80 healthy controls [62] . Similarly, other studies have also demonstrated that EPCs levels were lower in patients with diabetes mellitus type Ⅱ compared to healthy controls [63][64][65] . Treatment with strict glycemic control and total cholesterol improvement increased EPCs numbers [65] .…”
Section: Epcs and Diabetesmentioning
confidence: 58%
See 2 more Smart Citations
“…Enrolling 74 patients with type Ⅰ diabetes, EPCs counts were significantly lower in these patients compared to 80 healthy controls [62] . Similarly, other studies have also demonstrated that EPCs levels were lower in patients with diabetes mellitus type Ⅱ compared to healthy controls [63][64][65] . Treatment with strict glycemic control and total cholesterol improvement increased EPCs numbers [65] .…”
Section: Epcs and Diabetesmentioning
confidence: 58%
“…Similarly, other studies have also demonstrated that EPCs levels were lower in patients with diabetes mellitus type Ⅱ compared to healthy controls [63][64][65] . Treatment with strict glycemic control and total cholesterol improvement increased EPCs numbers [65] . There is strong evidence that patients with diabetes types Ⅰ and Ⅱ appear to have lower EPCs numbers compared to healthy controls.…”
Section: Epcs and Diabetesmentioning
confidence: 58%
See 1 more Smart Citation
“…86 In addition, a combination of statin and angiotensin receptor blocker seems to have a synergistic effect to increase the number and function of EPCs in DM. 85,87 Lifestyle modifications, including exercise 88 and weight reduction, 89 have also been shown to increase EPC number and function in patients with cardiovascular disease or DM.…”
Section: Approaches To Improve Epc Function and Survivalmentioning
confidence: 99%
“…In general the bone marrowderived EPCs in the diabetic patients are considered as dysfunctional, producing fewer endothelial cells and with reduced replicative and migratory potential [103]. As to fully divert the physiological role of EPCs in tissue repair and angiogenesis, the duet hyperglycemia-ROS stimulate the EPCs to produce pro-inflammatory cytokines and to shift NO production by elevating i-NOS and decreasing e-NOS [104]. As described for other cells, AGEs treatment disrupts EPCs physiology thus leading to a downregulation of e-NOS and Bcl-2 expression, as well as an elevation in cyclo-oxygenase-2, Bax, NF-ĸB, and caspase-3 in a MAPK (ERK/P38/JNK)-dependant manner [105].…”
Section: Diabetic Wound Endothelial Cellsmentioning
confidence: 99%